Urgensi Penalaran Hukum Dalam Pendidikan Hukum dan Implikasinya Terhadap Pemahaman Hukum - Suparno, Suparno (Law, Development and Justice Review, 2024)
The legal education system in Indonesia in practice applies logic and reasoning with scientific methods as a support in understanding the law. The writing of such an article aims to explore the understanding of reasoning in the legal field, in the form of general reasoning, specific reasoning in the form of legal reasoning models, and the implications of reasoning on legal understanding and consideration. The legal reasoning methods as referred to are categorized into two types, namely general reasoning in the form of reasoning with inductive, deductive, and abductive models or methods. The rest, there is specific reasoning, namely reasoning that is reviewed in terms of the school of legal philosophy. The use of models or methods of reasoning from these specifications is actually not separate from each other, but rather correlative and complementary. The application of such reasoning methods is actually aimed at developing the competence of prospective legal experts in understanding the law as a whole.